Sustainable banking : the greening of finance - Bouma, Jan Jaap; Jeucken, Marcel; Klinkers, Leon (Greenleaf Pub., 2001)
This comprehensive addition to the debate on sustainable development has been produced in order to take a global pulse on how the financial services sector is responding to the growing challenge of shareholder and stakeholder expectations on social and environmental performance. Given the intermediary role banks play within economies, their potential contribution toward sustainable development is enormous. To date, banks have been relatively slow to examine their exposure to risk and the business opportunities of sustainable development. Not before time, Sustainable banking concludes that this is beginning to change, with both risk and opportunity becoming established elements in banking policies towards environmental sustainability. The unprecedented scope of the book has attracted contributors including Deloitte & Touche, Rabobank, The World Bank, The European Bank for Reconstruction and Development, The United Nations Environment Programme, The World Business Council for Sustainable Development, UBS, Henderson Investors, KPMG, The World Resources Institute and SAM Sustainability.